How has the Eurozone Changed Since its Inception? - Pelle, Anita; Végh, Marcell Zoltán (Public Finance Quarterly, 2023)
The common European currency, the euro has existed since 1999; however, its introduction followed after decades of monetary integration and legal, economic and financial preparation. The first ten years of the monetary union were successful. The second decade was dominated by managing the crisis that was first global in character but then became limited to the crisis of the currency zone. In the initial phase, ad hoc type crisis management measures were taken; later, more systematic protection measures and institutional developments followed. Nevertheless, it is the resistance of the currency zone to future crises that has been established rather than its sustainability—the latter is yet to be ensured.